Institutional Legitimacy, Cross-Border Trade and Institutional Voids: Insights from the Cocoa Industry in Ghana. (February 2018) - Amankwah-Amoah, Joseph; Debrah, Yaw A.; Nuertey, Dorcas
Abstract: In spite of a growing body of literature on market opportunism in emerging markets, it remains unclear how supply chain partners abuse the institutional voids emanating from weak markets and legal enforcement mechanisms. This study attempts to integrate the concept of 'institutional voids' with that of 'opportunism in inter-firm relationship' literature to examine how they create space and conditions for illegitimate activities to occur in a supply chain. Using insights from cocoa production and distribution in Ghana, we uncovered activities such as tampering, adjustment of weighing scales and smuggling as examples of illegitimate activities and abuses in the supply chain. The study revealed that these activities are manifestations of institutional voids arising from weak markets and legal enforcement mechanisms. An analysis of the supply chain partners' activities illuminates our understanding of the underlying processes inherent in market opportunism. Taken together, the study demonstrates how smuggling and theft-to-smuggle have taken on new prominence as an escape response to the institutional voids in the country. The implications for future research are examined. Highlights: Explicate how institutional voids create space and conditions for illegitimate activities to occur in the supply chain. Examines the nature of institutional voids arising from weak markets and legal enforcement mechanisms. The roles of cocoa supply chain partners in the production and distribution networks are examined. The cocoa industry analysis is presented.